Aplicação de Sistemas de Informação Geográfica para o dimensionamento fotovoltaico urbano: um estudo de caso com o ArcGIS - Freitas, Breno Bezerra (2022)
The increase in the demand for electric energy and for forms of generation that cause less impact on the environment has been an increasingly recurrent subject around the planet. In this sense, an energy planning that considers more precisely the environment in which the source and the consumer are inserted has been debated. With this, the search for energy studies that evaluate the integration between renewable energy sources, distributed generation systems, and urban planning has brought the concept of Intelligent Energy Systems. One of the motivations for this trend is the strong growth of photovoltaic technology in cities, integrating generation and urban planning. Thus the present dissertation evaluates the functionalities of 20 computational tools considering 8 criteria: simulation capability, scenario generation, bottom-up, free or paid license, energy conditioning, urban PV application, integration with GIS and integration with cities master plans. Furthermore, a methodology for PV sizing and energy planning using the ArcGIS tool from aerophotogrammetry is proposed. As a form of validation, a case study was developed for a region in the city of Fortaleza (with area of 20,888 m²) and an annual electricity generation of 5.232 GWh was obtained in ArcGIS and 5.240 GWh with RETScreen, which represents a percentage difference of 0.15 %. Also as validation, the yield was compared between the sizing in ArcGIS and RETScreen with the LEA1 and LEA2 PV systems operating in Laboratório de Energias Alternativas da UFC (LEAUFC), obtaining the respective values of 4.42, 4.41, 4.40 and 4.39 kWh/kWp, obtaining percentage errors smaller than 0.7 %. Furthermore, it was realized that ArcGIS presents most of the evaluated functionalities, contemplating simulation capability, bottom-up, urban PV application, integration with GIS and integration with master plans for cities. Although it does not generate scenarios, requires paid license and does not apply power conditioning, it can be considered a tool for energy and urban planning, as well as shows great accuracy in PV sizing.